IMPROVING THE ORGANIZATION OF THE SHOVEL-TRUCK SYSTEMS IN OPEN-PIT COAL MINES - Mark KORYAGIN; Artyom VORONOV (Transport Problems, 2017)
The aim of the study is to reduce idle times of mining trucks and shovels in an open-pit coal mine. A heuristic algorithm for making dispatching decisions in conditions of dynamic allocation of trucks is developed. Priority parameters for choosing the shovel after the end-of-truck unloading are introduced. Also, an algorithm for searching for the optimal priority parameters to satisfy the required efficiency criterion is developed. This algorithm is based on a simulation model of a shovel-truck system. The proposed approach is applicable in terms of the group of shovels with a common dump point in various open-pit coal mines. The importance of this work lies in the fact that the proposed model takes into account the random factors related with the duration of loading and dumping, truck movement, repair of shovels and haul trucks, as well as the duration of periods between repairs.